Comparison of Reverse Hybridization, Microarray, and Sequence Analysis for Genotyping Hepatitis B Virus - Pas, Suzan D. (American Society for Microbiology (ASM), 2008)
Hepatitis B virus (HBV) genotyping has become important in epidemiological and clinical diagnoses, given the relationship between the viral genotype and the progression of disease or the appearance of antiviral resistance. Since genotyping by sequence and phylogenetic analyses is not convenient in the clinical setting, we evaluated InnoLipa HBV genotyping (Innogenetics, Belgium) and an HBV DNA-Chip (bioMerieux, France) prototype assay and compared their sequencing of the gold standard S gene, using a cohort of 275 individual patient samples. All but two samples, belonging to distant and individual subgroups within a single genotype, were detected by InnoLipa HBV assay. Four samples with dual infections belonging to genotypes A and G were identified only by InnoLipa HBV assay. Using an HBV DNA-Chip assay, one sample could not be amplified due to a low viral load. Four samples were identified as genotype C and two as genotype D by sequencing but were classified as genotype A (two samples) and D (two samples) and as A (one sample) and G (one sample) by the DNA-Chip assay. In conclusion, the InnoLipa HBV genotyping strip assay detected dual infections and was an easy and quick tool for genotyping, with a sensitivity of 99.3% and a specificity of 100% compared to sequence analysis. HBV DNA-Chip assay showed a sensitivity and specificity of 97.5 and 97.8%, respectively.